Investigation on the effect of bluff body ball on the combustion characteristics for methane/oxygen in micro combustor. (1st January 2020) - Pan, Jianfeng; Zhang, Chenxin; Pan, Zhenhua; Wu, Di; Zhu, Yuejin; Lu, Qingbo; Zhang, Yi
Abstract: A micro combustor inserted with a bluff body ball was developed and compared with the conventional combustor. The combustion characteristics (flammability limits, stable flame propagation and combustion efficiency) of methane/oxygen mixture in the micro combustor with bluff body ball were experimentally and numerically investigated. The results show that bluff body ball could broaden flammability limits of methane/oxygen mixture in the combustor. When inlet velocity was 0.7 m/s, the flammability limits in the combustor with 1 mm bluff body ball had equivalence ratios of 1.2 and 2.05 and that in the combustor with 2 mm bluff body ball had equivalence ratios of 1.5 and 2.68, which are larger than that in conventional combustors. The bluff body ball beneficially decreased the propagation velocity of the stable flame thereby making the gases burn completely. When the inlet velocity was 0.5 m/s, the combustion efficiency of the combustor inserted with a bluff body ball was 82.899% which was 2.7% higher than that of conventional combustor. However, the difference in combustion efficiency between the combustor with and without a bluff body ball decreases as the inlet velocity increases. When the velocity increased to 1.25 m/s, the difference was 0.75%. Highlights: Studied the effects of a bluff body ball on flame characteristics in micro combustor. The flammability limits in micro combustor with/without the bluff body ball are given. The effect of the bluff ball on flame propagation is analyzed experimentally. The 1 mm bluff body ball can improve the combustion efficiency by 2.7% at 0.5 m/s.